Mozambique: Agricultural R&D Indicators Factsheet - Flaherty, Kathleen; Nhamusso, Antonieta; Beintema, Nienke (Agricultural Research Institute of Mozambique, 2016)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also features a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges. This factsheet was originally published and translated in 2014 and updated in 2016.